2016
DOI: 10.1021/acs.energyfuels.6b01066
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oxide Scales Formed in the Naphthenic Acid Corrosion of Carbon Steel

Abstract: Naphthenic acid corrosion of steel is a major challenge in oil refineries. Iron sulfide scales, formed by corrosion due to sulfur compounds found in the crude oil, have shown unpredictable behavior when it comes to their protectiveness. Recent results show that simultaneous formation of an iron oxide scale formed by corrosion due to naphthenic acids may explain part of the variability and contribute to corrosion resistance of the scale formed on 5Cr steel. In depth analysis identified magnetite in the sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…Specimens for weight loss measurement were brushed to mechanically remove loose corrosion products, rinsed with acetone, exposed to the Clarke solution (ASTM G103) to dissolve the remaining corrosion products [17,18], dried again in N 2 gas flow, and finally weighed.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens for weight loss measurement were brushed to mechanically remove loose corrosion products, rinsed with acetone, exposed to the Clarke solution (ASTM G103) to dissolve the remaining corrosion products [17,18], dried again in N 2 gas flow, and finally weighed.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, carbon steel and organic acids form oil-soluble corrosion products ( eq 7 ), but due to the presence of active sulfur, the formed FeS protective film hinders the corrosion of steels by naphthenic acid to some extent ( eq 8 ). 17 , 23 , 30 , 31 …”
Section: Results and Discussionmentioning
confidence: 99%
“…In our prior research into the mechanism, a multilayer corrosion product scale was found to have an inner oxygen-containing layer underneath an outer sulfide layer after the concurrent sulfidation and NAC. , The inner layer (inner scale) was found to be a mixture of nanoparticulate magnetite and pyrrhotite while the outer layer (outer scale) was composed of pyrrhotite only. It was determined that the presence of magnetite in the inner scale significantly enhanced the layer protectiveness. The formation of magnetite in the inner scale was rationalized to be the result of thermal decomposition of iron naphthenates (iron carboxylates) formed by acid attack on the metal followed by the disproportionation of wüstite (FeO) trapped underneath the outer scale (reactions and ). …”
Section: Introductionmentioning
confidence: 94%
“…In our prior research into the mechanism, a multilayer corrosion product scale was found to have an inner oxygen-containing layer underneath an outer sulfide layer after the concurrent sulfidation and NAC. 16,17 The inner layer (inner scale) was found to be a mixture of nanoparticulate magnetite and pyrrhotite while the outer layer (outer scale) was composed of pyrrhotite only. It was determined that the presence of magnetite in the inner scale significantly enhanced the layer protectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation